A Survey on HIV/AIDS-Related Knowledge, Attitudes, Risk Behaviors, and Characteristics of Men Who Have Sex with Men among University Students in Guangxi, China. (15th June 2020) - Lai, Jingzhen; Pan, Peijiang; Lin, Yulun; Ye, Li; Xie, Long; Xie, Yuan; Liang, Bingyu; Zheng, Fangling; Chen, Rongfeng; Wen, Liufang; Luo, Yuxin; Liang, Hao; et al.
Abstract : In recent years, the prevalence of human immunodeficiency virus (HIV) infection among Chinese university students has increased significantly, and HIV transmission among men who have sex with men (MSM) comprises more than half of the new cases. There is still a lack of research investigating the incidence of male-to-male sex, the attitudes towards MSM, and the awareness of HIV/AIDS among university students in Guangxi, one of the HIV high-risk areas in China. Therefore, we performed a cross-sectional investigation among 578 male students, recruited by stratified sampling, in universities in Nanning, Guangxi, between January 2016 and March 2017. Researcher-administered anonymous questionnaires were completed. Self-recognition as MSM was found in 8.48% of the subjects. Compared with non-MSM, university student MSM included more people over the age of 20 (OR = 4.95 ), had less migration from other districts of Guangxi (OR = 0.26 ), and the majority were nonmedical students (OR = 8.99 ). In total, 63.25% of the male student participants reported a lack of acceptance of MSM, while 35.47% acknowledged barriers between themselves and acquaintances who were MSM. Overall, 67.30% of the subjects correctly answered questions related to AIDS knowledge. The proportion of MSM subjects who answered the AIDS-related questions completely correctly was significantly lower than that of non-MSM subjects (42.86% vs. 69. 57%, respectively, OR: 0.33), but the self-recognition risk of MSM was significantly higher than that of non-MSM (OR = 2.59 ). Risky behaviors associated with HIV infections, including smoking, alcohol consumption, drug abuse, and inconsistent condom use, were significantly higher among the MSM participants. The percentages of student's willingness to accept MC and PrEP were 70.93% and 77.51%, respectively. These results raise the alarm that university student MSM in Guangxi, China, require urgent public attention and more effective health education, including the education on MC and PrEP.